Therapeutic potential of allogeneic iPS cell-derived RPE transplantation for RPE65-LCA - Akiko Maeda; Daiki Sakai; Satoshi Yokota; Midori Yamamoto; Sunao Sugita; Yasuhiko Hirami; Michiko Mandai; Tadao Maeda; Masayo Takahashi; Yasuo Kurimoto (American Journal of Ophthalmology Case Reports, 2025)
Purpose: To evaluate the safety and therapeutic effects of induced pluripotent stem (iPS) cell-derived retinal pigment epithelium (RPE) transplantation for RPE65-associated Leber congenital amaurosis (RPE65-LCA). Observations: A 46-year-old male patient with RPE65-LCA underwent allogeneic iPS cell-derived RPE transplantation. The patient's best-corrected visual acuity (VA) prior to treatment was 2.0 (logMAR). A cell suspension of iPS cell-derived RPE was transplanted into the subretinal space. On day 15 post-transplantation, intraocular pressure (IOP) increased to 46 mmHg due to local steroid treatment, resulting in a decrease in VA to light perception (LP). Retinal imaging on day 71 revealed that most transplanted cells had migrated and formed an epiretinal membrane (ERM). The ERM was surgically removed on day 112. Two years post-transplantation, the patient reported improved vision, with VA improving to 1.4 (logMAR) from LP. Full-field stimulus testing (FST) and microperimetry demonstrated increased retinal sensitivity. These improvements have been maintained for up to 4 years post-treatment. Conclusions and importance: Although this case raised safety concerns regarding the use of cell suspension for RPE transplantation, RPE transplantation may still serve as a potential therapeutic option for patients with RPE65-associated retinopathy, particularly those who are not eligible or older age for RPE65 gene therapy.